Processing methods for high-amylase corn: impact on ruminal digestion and feedlot cattle performance - Horton, Lucas M. (Kansas State University, 2018)
Three studies evaluated effects of high-amylase corn (Enogen® Feed Corn, EFC) on ruminal digestive characteristics using different processing methods; a 4th study evaluated performance of finishing cattle fed steam-flaked EFC. In study 1, mill-run corn (CON) and EFC were ground through 9-, 6-, or 4 -mm screens, blended to contain 0, 33.3, 66.7, or 100% EFC, and heated to 50, 75, or 100⁰C (plus a non-heated control). No 2- or 3-way interactions occurred (P > 0.05). Increasing EFC in blends linearly improved in situ dry matter disappearance (ISDMD; P < 0.01) and in vitro gas production (IVGP; P = 0.02). Study 2 used blends of EFC and CON containing 0, 25, 50, 75, or 100% EFC, which were reconstituted to 27, 30, or 33% moisture, and ensiled. High-amylase corn did not affect ISDMD (P = 0.19) but IVGP increased linearly (P < 0.01) in response to greater amounts of EFC. Acetate:propionate ratio and total volatile fatty acid (VFA) production by in vitro fermentation improved linearly by increasing EFC (P < 0.02). Study 3 used the same blends of EFC and CON as study 2. Grains were tempered with 0, 3, or 6% moisture, steam conditioned 15, 30, or 45 min, and flaked. No 2- or 3-way interactions occurred. Starch availability, ISDMD, IVGP, and in vitro production of acetate, propionate, and total VFA increased linearly (P < 0.01) with greater flaked EFC in blends. Study 4 fed finishing diets consisting of steam-flaked CON, or EFC, for 136 d to 700 crossbred beef heifers (394 ± 8.5 kg initial BW). Compared to CON, cattle fed EFC had similar DMI (P = 0.78) but had greater ADG (P < 0.01) and a 5% improvement in feed efficiency (P < 0.01). Carcass weight was 6 kg greater for EFC cattle (P < 0.01), which also had 8% fewer liver abscesses (P = 0.03) than CON. Marbling score was greater in CON cattle (P = 0.04) than EFC; no differences in USDA Quality Grade (P = 0.33), Yield Grade (P = 0.13), LM area (P = 0.89), or 12th-rib fat thickness (P = 0.21) were evident. Improvements in digestion associated with EFC are likely confined to that component of grain mixtures due to a lack of quadratic effects. Improvements in feed efficiency, carcass weight, and potential liver abscess mitigation may be of advantageous use for producers.
Keywords: amylase; feedlot; high-amylase corn; steam-flaking